On the Optimization of Annular Plates Resting on Incompressible Liquid - Gasanova, D.D.; Shamiev, F.G. (Engineering Transactions, 1979)
The problem of minimization of weight is considered in the case of annular sandwich plates, statically indeterminate with respect to the support reactions and resting on an incompressible liquid; the plates are subjected to axi-symmetric loads, uniformly distributed over the annular region. Under various boundary conditions the fields of deflection rates and limit moments are calculated which correspond to the opitmum design; moreover, the reactions along the interior contour and relations between the loads and the pressure exerted by the liquid on the plate are derived. Numerical results are illustrated by graphs.